Risks of Methadone use as Substitute Therapy for Opioid Addiction during Pregnancy and use of Clonidine as a Plausible Alternative - Masroor Munim; Zafar Iqbal; David F Stowe (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2016)
The prevalence of illicit opiate use during pregnancy along with other substances has been increasing [1,2]. The prevalence of opioid abuse or dependence during pregnancy increased from 0.17% in 1998 to 0.39% in 2011 for an increase of 127% [3]. There is firm evidence that pregnancy outcome is worse in women using opiates than in the general population [1,4,5]. Deliveries associated with maternal opioid abuse or dependence compared with those without opioid abuse or dependence were associated with an increased odds (adjusted odds ratio) of maternal death during hospitalization, cardiac arrest, intrauterine growth restriction, placental abruption, length of stay more than 7 days, preterm labor, oligohydramnios, transfusion, stillbirth, premature rupture of membranes, and cesarean delivery [3]. Another problem for about 50% of neonates of opioid-addicted mothers is development of neonatal abstinence syndrome (NAS) requiring opiate treatment for opioid withdrawal after birth [6,7].